Role of myokines in regulation of a power exchange - V. I. Scherbakov; G. A. Skosyreva; T. I. Ryabichenko (Бюллетень сибирской медицины, 2012)
This review presents new data in respect of polyfunctioning of the muscular system. It is shown that the muscles are able to synthesize and секретировать миокины, with auto-couple-and endocrine effects. Is represented by the signal cascade, which runs the transcription of interleukin -6 (Il-6) in the skeletal muscles. For example, IL-6, as an important миокина, shown its metabolic and антивоспалительные effects at physical loads. Considered the issue of the specificity of the cytokine response in muscle contraction. This position is confirmed by the fact that, in эндотоксемии induced by the introduction of липополисахарида, the muscles begin to produce, as the IL-6, and factor of tumor necrosis α. The biological sense of the rise of production of IL-6 and other миокинов is that миокины are the communication system, the input signal of different organs and systems, primarily in the liver, adipose tissue, and immune and endocrine, subordinating their work requirements of long-term muscles flex.